Model Inkuiri Terbimbing Berbantuan Multimedia Interaktif Untuk Meningkatkan Penguasaan Konsep Fisika Peserta Didik - Syahriani Yulianci; Gunawan Gunawan; Aris Doyan (Department of Physics Education, Universitas Mataram, 2017)
The purpose of this study is to examine the effectiveness of learning use the guided inquiry model with interactive multimedia toward mastery of concept physics students. The study involved 68 students who were divided into two groups, the experimental group and control group. The research instrument used a mastery of concept physics students. Data were analyzed by using normalized gain scores. TheÃÂ result showed an increase in mastery of concept physics in both groups but experimental have the high increase more than control group. The result indicate that the guided inquiry learning with interactive multimedia is effective in enhancing mastery of concept physics students.